(untitled) (Bangladesh Journal of Bioethics, 2019)
In Past, Chinese traveler Fa-hien (14th century) to Ibn batuta (14th century) or from Nicola Kanti (15th century) to Queen Elizabeth (20th Century), every travelers and scholars are attracted by the charms and fame of Bangladesh. Ibn batuta described Bengal as “a hell full of bounties” and “wealthiest” land of the world”. But now a day, along this progress anxiety has proportionately increased. In this present age, science and technology are the easily available to common people. The world has come to a handful but yet people are still not so happy. As if the demand is insatiable. So, anxiety, apathy, intolerance, fear and panic are increased. Morality is deemed declining. Why immorality among young increased is a concern? Mark Twain said, “Always do what is right, it will gratify half of mankind”. What is right? a vantage point is needed to know. Our moral values which guide us and aids us in our conscious mobility in life. This article tries to find out the cause root of immorality among young generation and how to protect young generation from this moral deterioration.